1998
DOI: 10.1677/jme.0.0210179
|View full text |Cite
|
Sign up to set email alerts
|

Relaxin protein and gene expression in ovarian follicles of immature pigs

Abstract: Relaxin production by the ovarian follicle of gonadotropin-primed, prepubertal gilts is well documented. As far as we are aware, a source of relaxin in pig follicles, independent of gonadotropins, has not yet been reported. Therefore, the objective of this study was to determine whether relaxin is produced in porcine follicles in the absence of exogenous or cyclic gonadotropins. In immature pigs, immunoreactive relaxin was detected in fluids from small (1-3 mm), medium (4-5 mm) and large (>6 mm) follicles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…Its role in female reproduction is well known: relaxin is important during pregnancy and in preparation for parturition (Sherwood 2004), and it stimulates growth of the uterus in prepubertal animals (Bagnell et al 1993, Yan et al 2006. The main source of relaxin in females is the corpus luteum, but relaxin mRNA and/or protein have been detected also in preovulatory follicles (Bagnell et al 1993, Einspanier et al 1997, Ohleth et al 1998, and it has been suggested that relaxin exerts a paracrine or autocrine role in the ovary, promoting follicular growth and ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…Its role in female reproduction is well known: relaxin is important during pregnancy and in preparation for parturition (Sherwood 2004), and it stimulates growth of the uterus in prepubertal animals (Bagnell et al 1993, Yan et al 2006. The main source of relaxin in females is the corpus luteum, but relaxin mRNA and/or protein have been detected also in preovulatory follicles (Bagnell et al 1993, Einspanier et al 1997, Ohleth et al 1998, and it has been suggested that relaxin exerts a paracrine or autocrine role in the ovary, promoting follicular growth and ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…Relaxin mRNA expression in cultured GC and TC was monitored using semi-quantitative RT-PCR [3]. Briefly, 1 g total RNA was incubated at 37ЊC for 30 min in singlestrength MMLV-RT reaction buffer; 1.5 g random primers; 125 M of deoxy (d) ATP, dCTP, dGTP, and dTTP; 1 U deoxyribonuclease (DNase) (ribonuclease [RNase]-free); and 20 U RNasin (RNase inhibitor).…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
“…Each set of PCR reactions included the appropriate volume of the RT blank. A pool of follicle RNA from pigs 60 and 72 h after treatment with eCG, which contains relaxin mRNA [6], and liver from neonatal pigs were used as positive and negative controls for relaxin transcript, respectively [3]. The post-eCG follicle pool was included in each set of RT-PCR reactions to account for variability between each set of reactions.…”
Section: Reverse Transcription (Rt)-pcrmentioning
confidence: 99%
See 2 more Smart Citations